Effect of genotype and light intensity on somatic embryogenesis and plant regeneration in melon (Cucumis melo L.) - Kintzios, S.E.; Taravira, N.
The efficiency of 14 commercial cultivars of melon {Cucumis melo L.)for callus induction, plant regeneration and somatic embryogenesis under different photosynthetic photon flux densities (PPFDs)(150 or 50/imol m~^ s"')was investigated. Cotyledonal explants were cultured on a Murashige and Skoog (MS)medium supplemented either with 9.0/iM 2,4-dichlorophenoxyacetic acid and 23.2/iM kinetin or with 0.05 nM 2,4-dichlorophenoxyacetic acid and 0.26 piM 6-benzyladenine for the induction of somatic embryogenesis and shoots, respectively. For embryo maturation and root induction, growing callus tissues were transferred on growth regulator-free MS medium. Both genotype and the intensity of light significantly affected the rate of somatic embryogenesis, embryo maturation and plant regeneration. On average, 12-47 primary globular-stage embryos were produced per mm^ of explant surface. Fully developed, cotyledonary-stage somatic embryos were obtained from only three cultivars. Relatively high root induction rates were observed both on the shoot induction medium (11 cultivars)and on growth regulator-free medium (seven cultivars). In contrast, only six cultivars responded positively to the shoot induction treatment. Callus growth and somatic embryogenesis were significantly improved if cultures were incubated under higher PPFD values, although plant regeneration from all cultivars was significantly reduced under the same conditions.
Keywords: CUCUMIS MELO; CALLUS CULTURE; EMBRYO DEVELOPMENT; EMBRYO MATURATION; GENOTYPIC DIFFERENCES; LIGHT INTENSITY; ROOT INDUCTION; SHOOT INDUCTION; SOMATIC EMBRYOGENESIS